A tradução invertida em Jogos vorazes: um estudo sobre a fã - tradução e a tradução editorial - Gasparello, Evellyn (2021)
Translation studies and literary translation usually comprise a dynamic that implies the editorial translation first and possible (re)translations afterwards. However, that may change when certain literary works thrill fandom communities, who usually release unofficial translations for the delight of fans, and help setting the scenario for this study. In other words, the first translators of The Hunger Games are its fans. Therefore, fans and the professional translator take a central role for the analysis of Suzanne Collin´s dystopia, within a process of inverted translation process, that is, the fan translation is released before the official editorial version. Based upon Christiane Nord (2016), Lawrence Venuti (2002), and Rosemary Arrojo´s (2003) contributions for translation studies, our goal is to compare and analyze two translations of the first volume of the trilogy: the first one produced by the fandom and released in an online community, whilst the second was officially published by Rocco. Taking the context in which, each translation was produced [fans and editor] into account, we have selected and analyzed 14 different terms, which were foreignized by the fans, and domesticated by the editor. These terms were then submitted to readers-fans´ assessment, só that we could verify their preference for either a more foreignized or domesticated translation. This was carried out by means of a questionnaire, in order to investigate the readers´ preference for the fans (foreignized) or editor´s (domesticated) translation. Results highlight the preference for the domestication as it produces a more natural reading experience in the target language. To conclude, we present an interview with the editorial translator in which he reinforces invisibility and domestication as natural features for the translation process.